Correlación entre depresión al nacer con los marcadores bioquímicos para asfixia neonatal en el Hospital Belén de Trujillo - Euscategui Bobadilla, Rosa Emerita (2019)
Neonatal Asphyxia is a common perinatal event; in particular, in developing countries; This pathology causes multiorgan lesions, especially in the brain; leaving sequels that had a very complex and expensive treatment. Through this review of medical records of neonates with asphyxiation at birth, it will be possible to compare and establish whether there is a relationship between low Apgar at birth and the biochemical markers that are performed to rule out whether newborns have been affected by the asphyxiation chart. The question of this work is answered through a correlational cross-sectional and retrospective analytical study that involves collecting information through a data collection sheet to subsequently perform the analysis using the Chi-square statistical test (Chi2) to establish the relationship that It exists between Depression at birth with the Biochemical Markers for Neonatal Asphyxia.